A HUMANISTIC DA'WAH APPROACH TO PREVENTING INTOLERANCE, RADICALISM, AND TERRORISM: INTEGRATING THE FEMININE ATTRIBUTES OF GOD, LOCAL WISDOM, AND POLITICAL WILL - Risqiatul Hasanah; Hamdan; Ridhahani Fidzi; Hidayat Ma’ruf (Indonesian Journal of Islamic Communication, 2025)
Intolerance, radicalism, and terrorism constitute not only serious threats to social cohesion but also reflect the failure to internalize humanitarian values through the education system. Within the context of Islamic education, the urgency to offer approaches that engage spiritual, cultural, and structural dimensions has become increasingly evident. This article aims to explore the contribution of Islamic education in preventing and mitigating tendencies toward intolerance through the integration of the feminine attributes of the Asmaul Husna, local wisdom, and the political will of policymakers. The study employs a descriptive qualitative approach using library research, based on a critical analysis of relevant literature in Islamic studies, the sociology of education, and public policy. The feminine attributes of God, such as compassion, gentleness, and forgiveness, are elaborated as ethical foundations for shaping inclusive and tolerant learner character. Local wisdom, as a reflection of community culture and spirituality, is examined as a social force capable of strengthening national identity and refining religious practices. Political will is understood as a structural reinforcing factor that determines the direction of educational policy in institutionalizing religious moderation. The article concludes that the synergy among these three dimensions constitutes a strategic framework for developing a transformative, peaceful, and contextually responsive model of Islamic education.